PENGGUNAAN BIRTH BALL EFEKTIF DALAM MENGURANGI NYERI PERSALINAN KALA I - Elga Nurmaisya; Sri Mulyati (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2026)
Labor pain is a physiological condition experienced in childbirth, labor pain can affect the physical and psychological conditions of childbirth. Handling pain in labor can be  pharmacologically using pharmacological or non-pharmacological in the form of the use of birth balls. Non-pharmacological pain reduction techniques have the best effect for a short time, are inexpensive, and have no side effects. The role of midwives reduces the severity of pain and anxiety in women during childbirth and creates a positive birth experience, this can be realized by using non-pharmacological methods. Evidence Based Case Report aims to determine the effectiveness of birth balls on first stage labor pain. The method used is a Evidence Based Case Report. using pubmed and science direct, and 2 RCT articles have been critically reviewed. The results of the search showed that the birth ball method was effective in reducing pain in the first stage of labor, with a decrease in the pain scale from the range of 75-100 mm to 45-74 mm after the intervention for 30 minutes.